Wee Kim Wee Centre Celebrates 20 Years of Making Meaningful Impact - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The Wee Kim Wee Centre is celebrating its 20th anniversary with the opening of the new Wee Kim Wee Room housed at Singapore Management University and the launch of the Wee Kim Wee Heritage Fund.